2011
DOI: 10.1159/000324696
|View full text |Cite
|
Sign up to set email alerts
|

A New and Unusual Reciprocal Translocation in Cattle: rcp(11;25)(q11;q14–21)

Abstract: A new and unusual reciprocal translocation was detected in a heifer of the Agerolese cattle breed during a routine cytogenetic screening carried out on 13 animals (2 males and 11 females) kept at the ConSDABI Conservation Center in Benevento (Southern Italy). The 13 animals investigated had a normal karyotype except for a 1-year-old female, which carried one autosome smaller than the smallest normal bovine autosomes. This small autosome showed very little C-banding in comparison to the other autosomes, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…As described previously, the mother was a carrier of a balanced reciprocal translocation between chromosomes 11 and 25 [Perucatti et al, 2011]. The results of the newborn show a significant difference when compared to the mother's aberration.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As described previously, the mother was a carrier of a balanced reciprocal translocation between chromosomes 11 and 25 [Perucatti et al, 2011]. The results of the newborn show a significant difference when compared to the mother's aberration.…”
Section: Discussionsupporting
confidence: 59%
“…1 A). Anamnesis revealed that the mother, phenotypically normal, was a carrier of a t(11; 25)(q11,q14 ∼ 21) [Perucatti et al, 2011].…”
Section: Animalmentioning
confidence: 99%
“…A rare example has been found in a female calf with partial trisomy 11 and partial monosomy 25, which was unable to stand up and died after a few weeks (Table 2) [39]. The mother of this calf was a carrier of rcp(11;25) (Table 7) [41]. These two latter cases demonstrate that rcp cause reduced fertility by generating unbalanced embryos that die in early embryonic life or a few days after birth.…”
Section: Reciprocal Translocationsmentioning
confidence: 96%
“…A particular case has been reported in a calf of the Agerolese breed (southern Italy). This animal, unable to stand up and which died a few weeks after birth, was found to be affected by partial trisomy 25 and partial monosomy 11 [39] (Table 2) due to an unbalanced meiosis of the mother cow, which had been affected by a balanced rcp (11;25) and reduced fertility [41]. Two cases of trisomy involving BTA20 and BTA29 have been found using only genomic analyses [30,40].…”
Section: Autosomesmentioning
confidence: 98%
“…On the other hand, heterozygotes for several different reciprocal translocations have been detected in Bos taurus (Iannuzzi et al ., ; De Lorenzi et al ., , , ; Molteni et al ., ; Switonski et al ., ; Perucatti et al ., ) and in the water buffalo, Bubalus bubalis (Di Meo et al ., ), but these appear to be rare and have important detrimental effects on the carrier's fertility, and the viability of progeny (Switonski & Stranzinger, ). Some very rare autosomal translocations were described in horses that presented normal phenotypes but were apparently subfertile (Lear & Bailey, ).…”
Section: Chromosomal Rearrangements Associated With Polymorphisms In mentioning
confidence: 99%